Dixie and the Big Bully - Grace Gilman (New York, United States HarperCollins Publishers Inc, 2013)
Emma and Dixie are best friends. They do everything together and are always there for each other. But when Emma starts having trouble at school, she realizes that not everyone knows how to be a good friend. Can Dixie help?
Keywords: Level Reader -- Level Reader